Interaksi Obat Pada Pasien Diabetes Melitus Tipe 2 Dengan Penyakit Penyerta Di Rumah Sakit Otanaha Kota Gorontalo - Rasdianah, Nur; Hiola, Faramita; Andy Suryadi, A. Mu’thi; Gani, Athira Sri Wahyuni (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
As the numbers of cases continue to soar, diabetes mellitus or DM is one the most common disease in Indonesia. The WHO predicts that in 2030, numbers of diabetics in Indonesia will rise up to 21.3 million people, compared to 8.4 million people in 2000. Regarding the treatment, most of diabetes cases are commonly treated with pharmacological therapy. In this regard, polypharmacy and medications-related problems might occur during the treatment to control blood glucose level that is concurrent with the treatment of other diseases. Drug Interaction is a common medication-related problem. The present study is aimed to investigate the cases of drug interaction in patients with type-2 DM with comorbid diseases during the period of January-December 2019 in Otanaha Hospital, Gorontalo. As based on the inclusion criteria, the study involved 92 patients with type-2 DM and comorbid disease involved combination of metformin-glimepiride (47%), insulin (19%), metformin (14%), and glimepiride (9%). Moreover, based on the observation, minor interaction occurred the most (47%), followed by moderat interaction (31%) and major interaction. To sum up, the cases of drug interaction in patients with type-2 DM and comorbid disease in Otanaha Hospital, Gorontalo are relatively high. It is further concluded that the pharmacist's role is influential to supervise and monitor the patients medication intake.